Protective effect of the solvent extracts of Portulacca oleracea against acidified ethanol induced gastric ulcer in rabbits. (2nd January 2022) - Jan, Muhammad Shah Zeb; Ahmad, Waqar; Abdullah,; Kamil, Atif; Khan, Mir Azam; Rehman, Maqsood Ur; ullah, Irfan; Jan, Muhammad Saeed
Abstract: Portulacca oleracea L. has been used for treatment of different ailments. The aim of this study was to investigate the effectiveness and possible mechanism of action involved in the anti gastric ulcerogenic effect of Portulacca oleracea. Methanolic extract & subsequent fractions (100, 200 and 400 mg/kg) of Portulacca oleracea ( P. oleracea ) were administered orally to experimental rabbits one hour before oral administration of HCl/ethanol (40:60). Anti gastric ulcerogenic potential of P. oleracea was evaluated by assessment of gastric pH, pepsin, free acidity, ulcer index, mucus content and total acidity. For the investigation of possible mechanism of action malondialdehyde (MDA), histamine, and H + K + ATPase content were determined in the stomach homogenate. Histopathological study of stomach tissue was carried out by H&E dye. Ethyl acetate fraction (EAF) of P. oleracea was the most potent fraction among all fractions that exhibited efficient protection against acidified ethanol mediated gastric-ulcer. The ethyl acetate fraction (EAF) significantly increased the pH of gastric juice, while pepsin and histamine was observed to decrease significantly in comparison to acidified ethanol group (*** p ≤ 0.001). The EAF showed moderately H + K + ATPase inhibitory activity. Moreover, it was also observed that EAF decreased the malondialdehyde (MDA) level in the stomach tissue homogenate showing antioxidant effect. Histopathological studies showed that among the tested fractions, EAF significantly prevented acidified ethanol induced gastric mucosal damage. These results showed that mechanism of anti gastric ulcerogenic potential of P. oleracea could be associated with the reduction in histamine level, H + K + ATPase inhibition and reduced MDA level.